SOSIALISASI MINUMAN TEPACHE: FERMENTASI KULIT NANAS UNTUK GAYA HIDUP SEHAT DAN BERKELANJUTAN MASYARAKAT BATARA INDAH, TASIKMALAYA - Zahidatunnisa, Zahidatunnisa; Fitriani, Yuni; Oktoviyani, Seli Intan; Heryani, Neni; Rohmah, Pipah Hapipatur; Kusumawati, Puji; Kasman, Riska Nurmalasari; Arifah, Tiara; Maulani, Viana Amanda; Mulyani, Eva (LPPM Universitas Bina Bangsa, 2024)
This community service project focuses on introducing a pocket book about Tepache, a fermented drink made from pineapple peel, as an effort to improve healthy lifestyles and sustainability in the community of Perum Batara Indah, Kahuripan Village, Tawang District, Tasikmalaya City. The background to this activity is the lack of public knowledge about the health benefits of fermented foods and drinks. The aim of this service is to increase public awareness and knowledge about the health benefits of Tepache and teach how to make it. The service partners are the people of Perum Batara Indah who actively participate in this activity. The method used is service learning which consists of four stages: investigation, preparation, action and reflection. The investigation stage was carried out through a survey to identify community needs and knowledge. During the preparation stage, a pocket book was prepared containing information about the health benefits and how to make Tepache. The action stage includes socialization, demonstrations of making Tepache to the public in the form of videos and product testers. Reflection stage by giving response questionnaires to the implementation of socialization. The results of this activity show that the community gave a positive response and there was an increase in knowledge and awareness of healthy living. These activities demonstrate that culturally relevant health interventions are effective in promoting sustainable lifestyle changes. These results are important because they show the potential of using local resources to improve public health and environmental sustainability